Pore water pressure accumulation and settlement of clays with a wide range of Atterberg’s limits subjected to multi-directional cyclic shear - Nhan, Tran Thanh; Matsuda, Hiroshi (Vietnam Journal of Earth Sciences, 2020)
In this study, normally consolidated specimens on four clays with a wide range of Atterberg’s limits were tested by applying several series of undrained multi-directional cyclic shear followed by drainage. The cyclic shear tests were carried out under the shear strain amplitudes (γ = 0.05%-2.00%), number of cycles n = 200 and the phase difference θ = 90o. Then the accumulation of cyclic shear-induced pore water pressure and the post-cyclic settlement in strain (εv, %) were observed and discussed. In conclusion, it is clarified that the pore water pressure ratio (Udyn/σ’vo) increases with g and the soils with higher Atterberg’s limits show lower Udyn/σ’vo, and under the multi-directional cyclic shear strain at γ > 0.4%, Hue clay and Kaolinite clay with relatively low plasticity suffer from cyclic failure. In addition, the post-cyclic settlement has a tendency of decreasing with the Atterberg’s limits in the range of plasticity index from Ip = 25.5 to 63.8, meanwhile when Ip < 25.5, different tendencies were observed e.g., Hue clay (with lower Ip) shows a smaller settlement compared with those on Kaolin (with higher Ip). Furthermore, the threshold number of cycles (ntp) and cumulative shear strain (G*tp) for pore water pressure buildup were then clarified.